Having None of It: A Rebuttal to "Rape, Suicide, and the Rise of Religious Nones" - Speed, David ca. 20./21. Jh. (Journal of sociology and Christianity, 2025)
In the previous issue of this journal, Phillip Truscott published an article entitled "Rape, Suicide, and the Rise of Religious Nones" (2024) which found that the crude proportion of nonreligious individuals correlated with the crude rates of rape and suicide in the USA. He concluded that increases in the number of nonreligious individuals were causally linked to higher rates of rape and suicide. We note, among other things, that in his introduction he provides no meaningful justification for his thesis, he selected an odd analytical period, he erroneously treated self-control as the sole predictor of rape and suicide, his argument structure is logically fallacious, and he ignored or mischaracterized the extant literature addressing religion and attitudes towards rape. With respect to his analyses, he used simple correlation to advance a causal argument, he failed to consider reverse causality, he used an objectively incorrect analytical approach in several of his figures, and he mislabeled, misdescribed, or mischaracterized the content of one of his tables. As for his discussion, he significantly overstated the actual meaning of his results, he poorly defended why a causal relationship exists, and he mischaracterized the existing literature on drug consumption and rape to advance his argument that drug consumption mediated his observed findings. While Truscott’s research question was excellent, his work addressing said question was uniformly deficient.